Public Expenditure in the Slovak Republic : Composition and Technical Efficiency - Grigoli, Francesco (Washington, D.C. : International Monetary Fund, 2012)
Good practice suggests that budget allocations should reflect spending priorities and that spending should provide cost-effective delivery of public goods and services. This paper analyzes the composition of public expenditure in the Slovak Republic. It also assesses the relative efficiency of spending in education and health. The Slovak Republic spends more on social benefits and less on wages compared to the EU and OECD average. While it manages to translate the low expenditures into outcomes in an efficient manner in the education sector, this is not true for health. Moreover, the recent increases in expenditure levels have not improved outcomes, suggesting that significant budgetary savings could be achieved through increases in efficiency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet